Spatial Analysis Of Population Density, Altitude, Humidity, And Wind Speed With The Incidence Of Pulmonary Tuberculosis - Sakufa Marsanti, Avicena; Khoirina, Khusnul Fatimathul; Bachrun, Edy (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Globally, 89% of the population is infected with Mycobacterium tuberculosis. In East Java Province, there were 42,922 reported cases, with a treatment success rate of 44.7%, far below the minimum target of 80%. In Madiun District, the treatment success rate in 2022 was 73.31%, with a target of 85.66%. The number of tuberculosis cases in Madiun increased from 547 cases in 2021 to 995 in 2022, then slightly decreased to 968 in 2023. This study aims to analyze the spatial autocorrelation between environmental risk factors and the incidence of pulmonary tuberculosis in Madiun District. This is a quantitative study using an ecological spatial design and secondary data processed through the GeoDa Geographic Information System software. The study sample included pulmonary tuberculosis cases recorded in 15 sub-districts in Madiun District in 2022. The variables analyzed were population density, altitude, humidity, and wind speed. Based on the global univariate analysis using Moran's Index, the total number of tuberculosis cases in 2022 showed no spatial autocorrelation, as indicated by a p-value of 0.475 (>0.05) and a negative Moran’s Index of -0.1024, reflecting a dispersed or negative spatial pattern. The Local Indicators of Spatial Autocorrelation (LISA) analysis identified Kebonsari Sub-district as a hot spot area (quadrant I, high-high cluster). Bivariate LISA results showed significant local spatial autocorrelation (p-value < 0.05) between the incidence of pulmonary tuberculosis and the variables of population density, altitude, humidity, and wind speed. Among these, wind speed was the most strongly associated factor, with five sub-districts showing spatial autocorrelation. Kebonsari Sub-district, identified in the high-high cluster, is particularly vulnerable to tuberculosis transmission. It is recommended that pulmonary tuberculosis eradication and control programs be intensified, with priority focus on identified hot spot areas.